Effect of oxyresveratrol under in vitro lipopolysaccharide-induced periodontitis environment - Ju Ri Ye; Seung Hwan Park; Sang Wook Kang; Kyu Hwan Kwack; Yong Kwon Chae; Hyo-Seol Lee; Sung Chul Choi; Ok Hyung Nam (BMC Oral Health)
Abstract Background Oxyresveratrol is the main constituent of mulberries and has many bioactive properties beneficial to human health. The purpose of this study was to assess the anti-inflammatory effects of oxyresveratrol on in vitro periodontitis model. Methods Human periodontal ligament cells were treated with oxyresveratrol (0, 10, and 20 µg/mL) for 72 h. Cell viability and flow cytometry assays were performed. To investigate anti-inflammatory effect of oxyresveratrol on periodontal inflammation, nitric oxide production under lipopolysaccharide stimulation was assessed. Next, expression of biomarkers associated periodontal inflammation was evaluated. Scratch wound assay was performed to evaluate cell migration/proliferation potential of oxyresveratrol under lipopolysaccharide stimulation. Results Periodontal ligament cell toxicity was not observed in oxyresveratrol treatment. Oxyresveratrol treatment significantly inhibited nitric oxide production and reduced MMP-2, MMP-9, TNF-α, IL-6, and IL-8 expressions after lipopolysaccharide stimulation. Regarding cell migration/proliferation, open wound area in oxyresveratrol (33.28 ± 6.80%) was the lowest (p < 0.05). Conclusions Within the limits of this study, oxyresveratrol inhibited lipopolysaccharide-induced inflammation in periodontal ligament cells and promoted periodontal ligament cell migration/proliferation. These findings suggest that oxyresveratrol could be valuable for the management of periodontal diseases.